Measurement and Analysis of Natural Radioactive Elements in Salty Sediments from Central and Southern Iraq - Jasim, Mahdi Hadi; Ramadan, Afrah Essa; Hussain, Nessrian Ali (Iraqi Journal of Science, 2021)
Purification of fifteen NaCl samples from natural and different area in the middle and south of Iraq are prepared and studied the structural characteristics of samples by powder X-ray diffraction analysis at ð›Œ=1.542Ã…. The present work considered the specific activities of naturally occurring radioactive materials in salt samples, which are measured and analyzed using high resolution HPGe system. Also, the radiological parameters have been considered in this work. The average specific concentration (in Bq.kg-1) of the salt samples is found 16.864.92 for 226Ra, 5.972.05 for 232Th and 9.852.8 for 40K, respectively, which are below the national levels, 40Bq.kg-1, 30Bq.kg-1 and 400Bq.kg-1, respectively (UNSCEAR, 2000). Similarly the absorb dose rates are in the range3.71 nGy.h-1 to 12.591nGy.h-1.The measured radiation hazard indices show that the concentrations of these radionuclides in all samples are within the allowable limits.